INTENSITAS PERGERAKAN TRANSPORTASI DI DKI JAKARTA KEBIJAKAN PSBB DAN PPKM SELAMA MASA PANDEMI COVID-19 - Iskumaila Khoirunnisa; Mega Novetriskha Putri; Darmawan Listya Cahya; Dayu Ariesta Kirana Sari (LPPM Universitas Negeri Jakarta, 2022)
Currently, the conditions that are happening in Indonesia and even the world are, the outbreak of the Covid-19 virus (Covid-19 Pandemic), which has changed the arrangement in the activity of human social life. Based on the policies imposed, namely PSBB and PPKM by the government, it has an impact on human behavior patterns in daily life, especially in terms of transportation movements. This research will discuss these problems and raise